PENGARUH SERTIFIKASI DAN LISENSI TERHADAP PROFESIONALISME PEMANDU WISATA - Sukrispiyanto -; Nina Desinta Setiawati (STIE Indonesia Malang, 2020)
The purpose of this study is 1) to find out and analyze the effect of simultaneous partial certification and licensing on the professionalism of tour guides in the Tourism and Culture Office of Malang Regency; 2) To find out and analyze the effect of simultaneous certification and licensing on the professionalism of tour guides in the Malang Regency Tourism and Culture Office; 3) To find out and analyze which certification and licensing variables have the dominant influence on the professionalism of Tour Guides in the Malang District Tourism and Culture Office.In this study the sample used was a tour guide in the Department of Tourism and Culture of Malang Regency totaling 39 people. The results of this study were; 1) The effect of certification (X1) and License value (X2) influences Professionalism (Y) of 0.797 (79.7%) and the rest (1.68%) is influenced by other variables included in this research model. In this study, the results showed that the Beta value for the certification variable (X1) was 0.686 (68.6%) and the License variable value (X2) was 0.200 (20%) influencing Professionalism (Y), so in this study the certification variable (X1) amounting to 0.686 (68.6%) has a dominant influence on changes in Professionalism (Y) of tour guides in the Tourism and Culture Office of Malang Regency.